Tourism economics and policy. - Dwyer, Larry; Forsyth, P. (Peter); Dwyer, Wayne (Aspects of tourism texts;, 2020)
"This revised edition incorporates new material on the sharing economy, AI, surface and marine transport, resident quality of life issues, the price mechanism, the economic contribution of tourism, and tourism and economic growth. It remains an accessible text for students, researchers and practitioners in tourism economics and policy"--